Streptococcus pneumoniae Coinfection in COVID-19 in the Intensive Care Unit: A Series of Four Cases - Shrey Shah; Chaitanya Karlapalem; Pratik Patel; Nikhil Madan (Case Reports in Critical Care, 2022)
Bacterial coinfections in patients infected with SARS-CoV-2 pneumonia are uncommon, when compared to coinfections with other respiratory viruses. For example, the prevalence of bacterial coinfections in hospitalized seasonal influenza patients can exceed 30%, whereas the prevalence of bacterial coinfections in SARS-CoV-2 infection is less than 4%. Bacterial coinfections increase the severity of respiratory viral infections and have been associated with higher mortality and morbidity. Current literature shows that diagnostic testing and antibiotic therapy for bacterial infections are not necessary upon admission in majority of patients with SARS-CoV-2 patients. It is however important for the clinician to be cognizant of these coinfections since missing the diagnosis may pose a substantial risk to vulnerable COVID-19 patients. In that light, we present four cases of Streptococcus pneumoniae coinfections complicating confirmed SARS-CoV-2 infections.